2010
DOI: 10.1007/s00198-010-1230-5
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid-induced transient hepatotoxicity in a patient effectively treated for Paget’s disease of bone

Abstract: Bisphosphonate (BP)-induced hepatotoxicity is very rare. There are only a few reports of liver injury after BP treatment, including aledronate and risedronate in postmenopausal osteoporosis patients. We describe hereby the case of a patient with Paget's disease of bone accompanied by nonalcoholic fatty liver disease (NAFLD) who developed transient hepatotoxicity after zoledronic acid (ZOL) treatment. NAFLD had been diagnosed 1 year before presentation, based on liver ultrasonography (US). One day after infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Earlier two case reports have been noted in female patients diagnosed with postmenopausal osteoporosis and Paget's disease, demonstrating the transient rise in liver enzymes. No serious liver injury was implicated [16,17]. Compared to earlier published cases, by our knowledge, it is the first report of zoledronic acid associated hepatic injury in a male patient suffering from cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier two case reports have been noted in female patients diagnosed with postmenopausal osteoporosis and Paget's disease, demonstrating the transient rise in liver enzymes. No serious liver injury was implicated [16,17]. Compared to earlier published cases, by our knowledge, it is the first report of zoledronic acid associated hepatic injury in a male patient suffering from cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas, hepatotoxicity is a very rare side effect seen due to bisphosphonates with only a few case reports to support this evidence [12][13][14][15]. As per the literature search, hepatic damage solely due to zoledronic acid is an unusual outcome; especially in the absence of any pre-existing liver disease, concomitant medication implicated to cause hepatotoxicity, evidence in favor of zoledronic acid as an attributing factor for hepatic dysfunction is scanty and so far only two case reports have been reported [16,17]. A pre-clinical study carried in rats has shown biopsy-confirmed hepatotoxicity due to zoledronic acid administration [18].…”
Section: Discussionmentioning
confidence: 99%
“…This results in increased BMD through several antiresorptive mechanisms including inhibition of osteoclast recruitment, osteoclast activity on the bone, induction of osteoclastic apoptosis, and alteration of the bone or bone mineral to reduce dissolution rate . Risedronate, a novel orally administered pyridinyl bisphosphonate prescribed for the prevention or treatment of postmenopausal and glucocorticoid‐induced osteoporosis and Paget's disease, can reduce bone turnover and decreases resorption chiefly through osteoclastic effects, with no undesirable effects on cortical porosity or thickness or on cancellous bone volume . However, gastrointestinal (GI) effects of oral bisphosphonates are well observed and recognized and vary from mild nausea and heartburn to erosive oesophagitis and ulceration .…”
Section: Discussionmentioning
confidence: 99%
“…60 Risedronate, a novel orally administered pyridinyl bisphosphonate prescribed for the prevention or treatment of postmenopausal and glucocorticoid-induced osteoporosis and Paget's disease, can reduce bone turnover and decreases resorption chiefly through osteoclastic effects, with no undesirable effects on cortical porosity or thickness or on cancellous bone volume. 61,62 However, gastrointestinal (GI) effects of oral bisphosphonates are well observed and recognized and vary from mild nausea and heartburn to erosive oesophagitis and ulceration. 63 Prolonged treatment with alendronate has been associated with adynamic bone disease and atypical long bone fractures in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…While we may be familiar with more common side effects such as renal toxicity, flu-like symptoms (bone pain, arthralgia, fever, nausea, chills), atrial fibrillation and hypocalcaemia, there have been increasing number of case reports describing rare but significant complications associated with zoledronic acid use [5,6]. These include osteonecrosis of the jaw, orbital inflammatory disease, transient changes in thyroid function tests, transient hepatotoxicity, flare up of hand osteoarthritis and lifethreatening hyperkalaemia [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%